2019
DOI: 10.3390/su11216152
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Weekly Travel Patterns of Private Vehicles Using Automatic Vehicle Identification Data: A Case Study of Wuhan, China

Abstract: Automatic vehicle identification (AVI) systems collect 24 h vehicle travel data for the efficient management of traffic flows. The automatic vehicle identification data collected by an overhead traffic monitoring system provides a means for understanding urban traffic flows and human mobility. This article explores the weekly travel patterns of private vehicles based on AVI data in Wuhan, a megacity in Central China. We extracted origin–destination information and applied the K-Means clustering algorithm to cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The results reported in [29] confirm that time of day is associated with crash risk, but the differences between different crash types have not been investigated for drivers with different ages. Besides, older drivers' involvement in SCP crashes on weekdays was also different from that of younger and middle-aged drivers, which may be attributed to the fact that older drivers had different travel patterns in their retirement [41,42]. The authors of [21] reported that crash risk was the greatest at night on weekends, which is consistent with the SCP results on Sunday for the middle-aged and older drivers.…”
Section: Discussionmentioning
confidence: 51%
“…The results reported in [29] confirm that time of day is associated with crash risk, but the differences between different crash types have not been investigated for drivers with different ages. Besides, older drivers' involvement in SCP crashes on weekdays was also different from that of younger and middle-aged drivers, which may be attributed to the fact that older drivers had different travel patterns in their retirement [41,42]. The authors of [21] reported that crash risk was the greatest at night on weekends, which is consistent with the SCP results on Sunday for the middle-aged and older drivers.…”
Section: Discussionmentioning
confidence: 51%
“…It covers an area of around 8,494 km 2 and has a humid subtropical climate, with abundant rainfall in summer and four distinctive seasons [11]. By the end of 2018, the total number of registered motor vehicles in Wuhan was 2.97 million, accompanied by increasing urban traffic pressure [12].…”
Section: Sites Descriptionmentioning
confidence: 99%
“…This type of applications is intended to collect users' location data for various traffic statistics. They range from traffic monitoring [9]- [11], to traffic congestion assessment [12]- [14], to mobility pattern estimation [15]- [18], to dashcam data reporting [19]- [21]. These applications aim to capture data that accurately reflects the real-world traffic situation.…”
Section: Motivation a Traffic Data Collectionmentioning
confidence: 99%